2002
DOI: 10.1006/viro.2002.1376
|View full text |Cite
|
Sign up to set email alerts
|

Primary Isolated Human Brain Microvascular Endothelial Cells Express Diverse HIV/SIV-Associated Chemokine Coreceptors and DC-SIGN and L-SIGN

Abstract: Chemokines have received increasing attention due to their inhibitory activities on human immunodeficiency virus type-1 (HIV-1) and simian immunodeficiency virus (SIV) replication and the potential for chemokine receptors to assist in HIV-1/SIV entry into permissive cells. Besides CD4, which is the major receptor for HIV-1 and SIV, a number of chemokine receptors including but not limited to APJ, CCR3, CXCR4, and CCR5 may be coreceptors for HIV-1/SIV, not only in peripheral blood and lymphoid tissues but also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
54
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 72 publications
(71 reference statements)
6
54
0
1
Order By: Relevance
“…We found that BMECs express high levels of HSPGs likely contributed by syndecan-2 and -4. As expected, we did not detect CD4 or GalCer and found that BMECs express low levels of CXCR4 and CCR5, as previously described (47,57). Importantly, we found that like HSPGs, CSPGs are also abundantly expressed on the surface of BMECs.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We found that BMECs express high levels of HSPGs likely contributed by syndecan-2 and -4. As expected, we did not detect CD4 or GalCer and found that BMECs express low levels of CXCR4 and CCR5, as previously described (47,57). Importantly, we found that like HSPGs, CSPGs are also abundantly expressed on the surface of BMECs.…”
Section: Discussionsupporting
confidence: 89%
“…CXCR4 and CCR5 inhibitors did not block pNL-ADA or pNL-HXB attachment to BMECs (Fig. 6A), in agreement with previous work by Liu et al and Mukhtar et al, who showed that SDF-1␣, RANTES, and MIP-1␣ and ␤ do not prevent HIV-1 binding to BMECs (47,57). Together, these results indicate that HIV-1 uses receptors other than CXCR4 and CCR5 to initially attach to the surface of BMECs.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…This unique coreceptor has been shown to bind and allow infection of cells by a number of HIV-1 strains. [61][62][63][64] Its presence in the central nervous system siRNA and CXCR4 N Zhou et al (CNS) is of potential importance, [64][65][66] and investigation of siRNAs' effects on this moiety is ongoing in our laboratories. CXCR4, as well, has been demonstrated on CNS-based cells.…”
Section: Discussionmentioning
confidence: 99%
“…CXCR4, as well, has been demonstrated on CNS-based cells. 66,67 It has been recently demonstrated that RNAi also functions in mammalian neurons in vitro. 68 As such, targeting CXCR4 and/or APJ in human CNS cells may be an important first step in targeting RNAi toward HIV-1-induced encephalopathy.…”
Section: Discussionmentioning
confidence: 99%